2015
DOI: 10.3390/ijms161025450
|View full text |Cite
|
Sign up to set email alerts
|

TP53inp1 Gene Is Implicated in Early Radiation Response in Human Fibroblast Cells

Abstract: Tumor protein 53-induced nuclear protein-1 (TP53inp1) is expressed by activation via p53 and p73. The purpose of our study was to investigate the role of TP53inp1 in response of fibroblasts to ionizing radiation. γ-Ray radiation dose-dependently induces the expression of TP53inp1 in human immortalized fibroblast (F11hT) cells. Stable silencing of TP53inp1 was done via lentiviral transfection of shRNA in F11hT cells. After irradiation the clonogenic survival of TP53inp1 knockdown (F11hT-shTP) cells was compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Our results, along with previous studies, have indicated that both TP53INP1 and TOMM40 were related to AD [69,70] and T2D [50,63], whereas C8orf38 was identified as a novel gene for T2D. The TP53INP1 encodes a protein for mediating autophagy-dependent cell death through apoptosis and regulating cellular-extracellular matrix adhesion and cell migration [77], and was expressed by activation via p53, which regulated the oxidative damage response [78]. A study with mice genetically engineered knockout for TP53INP1 demonstrated that the impaired mitophagy of dysfunctional mitochondria is the main source of the chronic oxidative stress, and may cause insulin resistance and promote the predisposition to T2D [79].…”
Section: Discussionsupporting
confidence: 75%
“…Our results, along with previous studies, have indicated that both TP53INP1 and TOMM40 were related to AD [69,70] and T2D [50,63], whereas C8orf38 was identified as a novel gene for T2D. The TP53INP1 encodes a protein for mediating autophagy-dependent cell death through apoptosis and regulating cellular-extracellular matrix adhesion and cell migration [77], and was expressed by activation via p53, which regulated the oxidative damage response [78]. A study with mice genetically engineered knockout for TP53INP1 demonstrated that the impaired mitophagy of dysfunctional mitochondria is the main source of the chronic oxidative stress, and may cause insulin resistance and promote the predisposition to T2D [79].…”
Section: Discussionsupporting
confidence: 75%
“…How Hh signaling regulates GDF15 expression is unclear. The expression of GDF15 is regulated by p53 pathway 33 , and Trp53inp1 was required for IR-induced maximal elevation of GDF15 expression in human fibroblasts 34 . Since transient Hh activation did not repress the upregulation of Trp53inp1 and other p53 target genes including p21 and Mdm2 by IR on day 7 (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…We found several genes involved in the development of the nervous system and eliciting response to stress, indicating the importance of the neuroendocrine system in activating stress response in the candidate regions. One of the genes, DMBX1 is involved in brain and sensory organ development 49 , 50 while TP53INP1 is a key cell stress response protein with antioxidant function 51 , 52 . Through its interaction with the ERK1 and p38 mitogen-activated protein kinases, MKNK1 may play a role in responding to environmental stress and control cytokine production and delayed apoptosis 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%